Postoperative blood loss in coronary surgery. No real impact of fibrinolysis detected by thromboelastography and D-dimers. A prospective, randomized study - Šnircová, Jana; Jareš, Martin; Malý, Marek; Straka, Zbyněk; Špegár, Ján; Vaněk, Tomáš (International heart journal, 2008)
Although in many cardiac surgery centers pharmacological strategies based on fibrinolytic inhibitors are used on a routine basis, detailed knowledge of fibrinolysis during various settings of coronary surgery is still limited. Sixty-five patients scheduled for coronary surgery were randomized into 3 groups: group A--conventional coronary artery bypass grafting, group B--off-pump surgery, and group C--coronary artery bypass grafting with modified, rheoparin coated cardiopulmonary bypass with the avoidance of reinfusion of cardiotomy blood into the circuit. The sampling time points for rotation thromboelastographic evaluations were as follows: preoperatively, 15 minutes after sternotomy, on the completion of peripheral bypass anastomoses, at the end of the procedures, and 24 hours after the end of surgery. D-dimer levels were evaluated before surgery, at the end of procedures, and 24 hours after surgery. Thromboelastographic signs of fibrinolysis (evaluated by Lysis Onset Time-intergroup differences at 60 and 150 minutes of assessment: P = 0.003 and P < 0.001, respectively) were clearly detectable during cardiopulmonary bypass in group A, but not at any time in groups B and C. At the other sampling times all thromboelastographic parameters were similar in all groups. In group A, no exceptional bleeding tendency (during 24 hours), as compared to groups B and C (geometric means and 95% confidence intervals: group A: 686.7 [570.8; 826.1] mL, group B: 555.3 [441.3; 698.9] mL, group C: 775.6 [645.1; 932.3] mL, P = 0.157), and no significant correlations between Lysis Onset Time, postoperative blood loss, and D-dimer levels were found. No significant differences in postoperative blood loss related to cardiac surgeons and assistant surgeons were detected. Thromboelastographic signs of increased fibrinolysis were detectable in the important proportion of coronary surgery patients operated on with the use of conventional cardio-pulmonary bypass, but not in off-pump patients and those operated on with the biocompatible surface-modified circuit without reinfusion of cardiotomy suction blood. These signs resolved spontaneously at the end of surgery and were not associated with increased postoperative bleeding. No significant correlation with D-dimer levels was found.
Keywords: financování organizované; fibrinolýza; Female; koronární bypass bez mimotělního oběhu; tromboelastografie; fibrin-fibrinogen - produkty degradace; ženské pohlaví; lidé; Coronary Artery Bypass, Off-Pump; Postoperative Hemorrhage; Thrombelastography; Fibrin Fibrinogen Degradation Products; Financing, Organized; prospektivní studie; pooperační krvácení; Male; Fibrinolysis; Aged; Prospective Studies; koronární bypass; senioři; mužské pohlaví; Coronary Artery Bypass; Humans